Impact of parity and salivary hormonal levels on motivation toward infant emotions. - Sinisalo, Hanneli (2024)
Infant faces have been shown to be particularly motivating stimuli for women. No studies, however, have compared mothers and nonmothers in whether parity modulates approach motivation toward emotional infant faces. We studied 54 Finnish first-time mothers and 42 nonmothers in a pay-per-view key-press task wheretheparticipants wereshown20infantfaceswithsmilingandcryingexpressions.Participantswere able to adjust the time each face was visible. In addition, salivary testosterone, estradiol, and cortisol levels were measured and their impact on motivation toward infants analyzed. When controlling for the hormonal levels, happy infant faces were viewed longer than crying faces and there was no difference in mean viewing times between mothers and nonmothers. An interaction between parity and emotion emerged: Mothers were more motivated to view happy faces and less motivated to view crying infant faces than nonmothers. Testosterone had a significant effect on viewing times: The higher the testosterone levels were, the shorter amount of time infant faces were viewed. This indicates that testosterone is inversely associated with approach motivation to emotional infant stimuli. This study is the first to compare mothers and nonmothers in a task measuring motivational responses to infant stimuli and indicates that the difference between the approach motivation caused by happy and distressed infant emotions might be more heightened in new mothers.